Analisis Kreatif Ide dan Pesan (Studi Kasus Terhadap TVC “Instagram Boyfriend” Ichi Ocha) - Clara Cahya Octaviani Setiawan; Gregorius Genep Sukendro (Prologia, 2021)
Television is a medium that still diverts advertising spending from media convergence to digital. There are many advantages of advertising on television, as well as their shortcomings. One drawback is the free control of the audience to change channels. Therefore, it is important for advertisers to ensure that their ads generate a special appeal so that the audience is interested in watching. Two important things that make an ad interesting are the ideas and the message. A 'creative' idea has five important components, namely a strong strategy, a strong sales idea, always relevant, stands out, and can be built into the campaign. The message that is 'creative' has three important points, namely stopping power, striking power, and sticking power. In this case, ideas and messages in an advertisement have a related and complementary relationship with each other. Ideas and messages are mutually sustainable. In this context, the important thing to consider in creating an advertisement is not to get one of the ideas or messages dominate and cover the other.Televisi adalah media yang masih mendominasi belanja iklan terlepas dari konvergensi media ke arah digital. Ada banyak kelebihan dari pemasangan iklan di televisi, begitu pula kekurangannya. Salah satu kekurangannya adalah kontrol bebas audiens untuk mengganti saluran. Oleh karena itu, penting bagi pemasang iklan untuk memastikan bahwa iklan mereka produksi memiliki daya tarik tersendiri agar audiens tertarik untuk menyaksikannya. Dua hal penting yang membuat iklan menarik adalah ide dan pesannya. Ide yang ‘kreatif’ memiliki lima komponen penting, yaitu potent strategy, strong selling idea, always relevant, stands out, dan can be built into campaign. Pesan yang ‘kreatif’ memiliki tiga poin penting, yaitu stopping power, striking power, dan sticking power. Dalam hal ini, ide dan pesan dalam sebuah iklan memiliki hubungan yang berkaitan dan saling melengkapi satu sama lain. Ide dan pesan saling berkesinambungan satu sama lain. Dalam konteks ini, hal yang penting untuk diperhatikan dalam membuat sebuah iklan adalah jangan sampai salah satu ide atau pesan tersebut mendominasi dan menutup satu dan yang lainnya.